Effect of Local Lactic Acid Bacterial Isolates as Probiol for Microbiota Population Balance of Fish Intestine - Fawzia Jassim Shalsh; Iman Sabea Khamees; Nagha Abdul Alrazzag; Imad Ibrahim Ali Al-sultan (Hasanuddin University, 2025)
The purpose of this study was to investigate the cell surface hydrophobicity of four Lactic acid bacteria (LAB) strains isolated from various traditional and industry fermented yogurt and cheese sources based on the biochemical tests. The determining cell surface hydrophobicity is a critical step in selecting LAB strains with probiotic qualities and is one of the most essential elements regulating LAB's particular adherence to abiotic surfaces, as well as one of the most critical factors controlling LAB's absorption and destruction of hydrophobic organic matter. In current study, the four LAB strains had high cell surface hydrophobicity to the four separate hydrocarbon solvents xylene, hexadecane, chloroform, ethyl acetate determined via spectrophotometer at 450 nm. The highest hydrophobicity score was determined for LB3 for chloroform, n- hexadecane, ethyl acetate and xylene at 66.51, 38.23, 33.67 and 24.18% respectively. LB3 demonstrated promising cell surface characteristics, suggesting that it could be used as an indigenous probiotic.